SOCIAL ENTREPRENEURSHIP IN THE MODERN BUSINESS ENVIRONMENT: DEFINITION, DEVELOPMENT FACTORS, AND GLOBAL EXPERIENCE - Zelisko , Н. (Bulletin of Lviv National Environmental University. Series "AIC Economics", 2025)
The article examines the theoretical and practical aspects of social entrepreneurship development as an essential element of the modern economic system. The key approaches to defining social entrepreneurship, its features, functional characteristics, and impact on socio-economic development are outlined. The study examines the factors that influence the development of social entrepreneurship in an unstable economic environment and amid globalisation, highlighting the critical roles of funding, state support, legal regulation, and innovative technologies. The study explores the global development of social entrepreneurship, focusing on implementation models within the European Union, the United States, and other advanced economies. It pays special attention to how these models can be adapted to the realities in Ukraine and identifies key challenges faced by social entrepreneurs in the country. The main obstacles hindering the active development of this sector in Ukraine include an underdeveloped regulatory framework, difficulties in securing financing, a lack of systematic government support, and low public awareness of social entrepreneurship. Based on this analysis, the study offers recommendations to stimulate social entrepreneurship in Ukraine. Key directions include creating a favorable legal environment, expanding access to investment resources, introducing educational programs on social entrepreneurship, and integrating socially responsible business practices into the country's economic policies. The research findings can be utilised by entrepreneurs, government agencies, non-governmental organisations, and researchers to develop effective support strategies and promote social entrepreneurship. These conclusions contribute to a broader understanding of social entrepreneurship as a key driver of sustainable development in modern economies and societies. Keywords: social entrepreneurship, business environment, social mission, innovation, sustainable